Sustainable Management Of Household Organic Waste Through Vermicomposting: Evaluating The Nutrient Potential And Financial Sustainability - Giri, Sujata; Baral, Suresh; Khanal, Rishav; Gautam, Prakash; Tiwari, Saugat; Baral, Sanjay (Journal of Advanced College of Engineering and Management, 2026)
Solid waste management is becoming a major environmental challenge for sustainable development, especially in developing countries due to urbanization, industrialization, and improper dumping practices. Waste management techniques such as recycling, incineration, landfilling, and composting are designed to manage waste materials to reduce environmental impact. This study examines the nutrient composition and economic viability of household-scale vermicomposting using organic waste in Shuklagandaki Municipality, Tanahun. A 90-day bin experiment was carried out using Eisenia fetida earthworms, with kitchen waste, garden residues, and paper serving as feedstock. The findings indicate that vermicompost meets standard nutrient criteria for nitrogen, phosphorus, and potassium, though moisture content and pH are slightly above recommended levels. The economic analysis showed strong financial feasibility, with a net present value of NRs. 801,460 over five years at a 6.05% discount rate. Sensitivity analysis identified investment cost and annual benefits as the key factors influencing project viability. Household survey results (n = 109) indicated an estimated daily organic waste generation of 8,866 kg. Overall, the findings suggest that vermicomposting is a practical, environmentally sustainable, and economically viable approach for managing household organic waste in municipalities.